Определение нейтронно-физических характеристик слабопоглощающих сред; Известия вузов. Физика; Т. 58, № 12-3 - Кузнецов М. С. Михаил Сергеевич; Монгуш С. А. Светлана Амыровна; Семенов А. О. Андрей Олегович; Чуйкина А. В. Анастасия Владимировна; Чурсин С. С. Станислав Сергеевич (2015, 2015)
Заглавие с экрана